A qualitative study on personal hygiene knowledge and practices among food handlers at selected primary schools in Klang Valley area, Selangor, Malaysia - Tan, Siew Lian; Cheng, P. L.; Soon, H. K.; Ghazali, Hazrina; Mahyudin, Nor Ainy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
A study was conducted to determine personal hygiene knowledge among 25 food handlers at 12 selected primary schools in Klang Valley area, Selangor, Malaysia. A qualitative approach using in-depth interviews was employed and respondents were selected by a convenience sampling. The results showed that the respondents had basic knowledge on personal hygiene practices, mainly on hand washing (30.7%) and glove use (18.7%). The food handlers (<11%) also demonstrated their knowledge on other good personal hygiene practices that were related to the use of hair restrain/cap/apron, keeping tidy hair/ clean nails/ clean hand, no bare hand contact with food, not wearing ring/jewelry, no smoking, tidy/clean attire and typhoid injection. Further assessment demonstrated that only 12% respondents were able to describe a reasonable procedure for hand washing and the steps that were missed most were the failure to specify the need to rinse and dry hands after washing. The respondents knew that the use of glove was to prevent bare hand contact (80%) and can reduce risk of food contamination (88%). All the respondents agreed that food handlers with abrasion or cuts on their fingers or hands should not touch unwrapped foods. A high percentage respondents (>90%) practiced various good hand washing practices, with only 36% did not practice washing hands after eating or drinking. Most respondents (>70%) practiced glove use, however more than 50% did not wash hands with every glove change, change gloves when change type of products and after preparing raw material. The study showed that the food handlers have basic knowledge one good personal hygiene practices. However, some discrepancies were revealed in the proper hand washing procedure. This study recommended good hand washing procedure to be reiterated among the food handlers. There is also an immediate need for continuous training among food handlers regarding good personal hygiene practices.